Expression and clinical significance of Klotho protein in serum, umbilical cord blood, and placenta of pregnant women with intrauterine growth restriction - Zeng, Guixiang; Lian, Jingjing; Shen, Jiajia; Shi, Yuan (Frontiers in Pediatrics, 2025)
ObjectivesIntrauterine growth restriction (IUGR) significantly affects neonatal development, but its pathogenesis is not fully understood. Klotho protein is involved in aging-related diseases, and its role in fetal growth is unclear. This study aims to explore Klotho's role in IUGR.MethodsA case-control study was conducted at Nanning Maternal and Child Health Care Hospital from July 2023 to June 2024. Fifty-two neonates (gestational age ≥34 weeks and <42 weeks) were divided into the appropriate for gestational age (AGA) group (n = 30) and the IUGR group (n = 22). Venous and umbilical cord blood were collected to measure Klotho, growth hormone (GH), and insulin-like growth factor 1 (IGF-1). Placental tissues were examined for histopathology and immunohistochemistry.ResultsThe IUGR group showed placental morphological changes, including increased syncytial knots and inflammation. Klotho expression in placental tissue was significantly reduced (p < 0.0001), while IGF-1 levels increased (p < 0.001) and GH levels decreased (p < 0.001). Soluble α-Klotho levels were lower in maternal venous blood (p < 0.0001) and umbilical cord blood (p < 0.01). GH and IGF-1 levels in maternal venous blood and umbilical cord blood were altered in IUGR cases.ConclusionsReduced Klotho expression in IUGR cases, along with changes in GH and IGF-1, suggests disruptions in metabolic processes affecting fetal growth and development. These findings suggest a potential involvement of Klotho in placental changes and fetal development, warranting further mechanistic studies.